GIS-based watershed characterization and morphometric analysis in Bohol Watersheds, Philippines - Imelida Torrefranca; Roland Emerito Otadoy (Geology, Ecology, and Landscapes)
The study presents a GIS-based morphometric analysis characterizing the watersheds in Bohol, Philippines. An IfSAR-derived DEM data were processed and used to delineate the watersheds and evaluate morphometric parameters in QGIS/QSWAT. The analysis revealed that Loboc Watershed (LW) and Wahig-Inabanga Watershed (WIW) were sixth-order watersheds. Covering 675 km2 (LW) and 610 km2 (WIW), the watersheds encompassed about 34% of the mainland area. The bifurcation ratios, 3.91 (WIW) and 4.06 (LW), suggested highly dissected watersheds with high flood peaks. LW has low permeability, and high runoff and erosion susceptibility compared to WIW, as indicated by higher values for the form factor, circulatory ratio, drainage density, and stream frequency. The ruggedness numbers of 1.653 (WIW) and 1.457 (LW) indicated steep slopes in WIW than in LW, associated with high erosion and environmental degradation. The hypsometric integral of 0.22 (WIW) and 0.37 (LW) implied lesser erosional areas in WIW than in LW. The study found that both watersheds were highly susceptible to erosional processes. The two watersheds performed critical environmental functions on Bohol Island; hence, the results of this study present a piece of baseline information for resource managers to conduct further investigations that would identify hotspot areas and enable targeted soil and water conservation initiatives.